Preparation of Mesoporous/Microporous MnCo2O4 and Nanocubic MnCr2O4 Using a Single Step Solution Combustion Synthesis for Bifunction Oxygen Electrocatalysis. Issue 5 (15th January 2020) - Ashok, Anchu; Kumar, Anand; Ponraj, Janarthanan; Mansour, Said A.
Abstract : We report the synthesis of mesoporous/microporous MnCo2 O4 and cubic MnCr2 O4 using solution combustion synthesis for oxygen reduction and oxygen evolution reactions. XRD and TEM analysis indicate small crystallites of MnCo2 O4 forming ultra-thin layer of irregular structures that lead to porous morphology. A slightly larger crystallite size was observed for MnCr2 O4 . The surface oxygen defect in MnCo2 O4 is much higher than MnCr2 O4 that enhances the active sites for the oxygen adsorption and promotes fast dissociation in presence of more exposed Mn/Co sites during the oxygen electrocatalysis. The electrochemical properties of the synthesized catalysts were analysed using CV, LSV, EIS and CA showing high limiting current density and kinetic current density, positive onset and halfwave potential and higher number of overall electron transfer in MnCo2 O4 that MnCr2 O4 . Chronoamperometric (CA) runs for 24 h shows excellent stability of MnCo2 O4 without any significant decrease in the current or potential value in ORR and OER. On basis of the activity and stability performance, MnCo2 O4 shows to be a promising bifunctional electrocatalyst, with significantly improved performance than previously reported Mn and Co mixed oxides, and comparable to Pt and Ru based catalysts in terms of durability, onset potential and Tafel slope.